No limite da cruz e da enxada: imbricamento contemporâneo entre o MST e o cristianismo da libertação em Ribeirão Preto - Guidotti, João Victor Martins Toledo (Universidade Federal de São Carlos, 2025)
This dissertation examines the complex intersection between Liberation Theology (TL) and the Landless Rural Workers' Movement (MST), using the Mário Lago Settlement, located in Ribeirão Preto, São Paulo. To do this, we compared the work of TL when the settlement was formed in 2003 with the work of the same movement today, 22 years later. TL, with its historical roots in Latin America, represented a theological and pastoral response to the conditions of inequality and oppression experienced by marginalized populations, particularly in rural areas. For its part, the MST emerged in Brazil as an organized social movement, structured around the struggle for land reform. The interaction between these two forces was striking at various historical moments, especially in the context of the strength of the Basic Ecclesial Communities (CEBs) and the formation of the movement's organizational bases. Adopting a sociological approach that combines historical, structural and empirical analysis, this work stems from the quest to understand the transformations in the religious and community field following the decline of the TL. The research explored how this ebb and flow has impacted the social and political dynamics of the Mário Lago Settlement, a space which in the past was marked by the presence of pastoral leaders aligned with the TL, but which today faces the absence of equivalent figures in their militant role. The analysis also considers how the lack of continuity of this pastoral model has contributed to a process of fragmentation of Catholicism, and consequently to the significant advance of Pentecostalism in this region.
On the edge of the cross and the hoe: contemporary imbrication between the MST and liberation christianity in Ribeirão Preto
Keywords: Teologia da Libertação; MST; Catolicismo rural; Pentecostalismo; CIENCIAS HUMANAS::SOCIOLOGIA